Estimasi Gas Rumah Kaca pada Berbagai Macam Pengelolaan Air Menggunakan Model Denitrifikasi-Dekomposisi (DNDC) - Arif Rahmat; Chusnul Arif; Yudi Chadirin (Balai Teknik Irigasi, 2018)
Escalation of the scarcity in water resources has stimulated the development of a different method to preserve water in the paddy field. Several studies have been carried out simultaneously to observed the effectiveness of various water regimes on sustaining water, mitigating greenhouse gases (GHG), and maintaining rice yields. Irrigation management is a critical factor in controlling Methane (CH4) and Nitrous oxide (N2O) emission in the paddy field. The aim of this research is to evaluate the Denitrification-Decomposition (DNDC) Model in estimated greenhouse gas from various water regime management. This research conducted from January until May 2018, in plot experiment used SRI method under three different water regimes: flooding regime (RT), wet regime (RB), and dry regime (RK). DNDC Model was created to predicted CH4 and N2O emission in the agricultural ecosystem. This model already used and evaluated in subtropical land, but the ability of this model still needs to evaluate for soil in the tropical area such as Indonesia. The emission result showed a different pattern between the simulation model and observation model. The coefficient of determination (R2) from CH4 and N2O emission simulation with actual fluxes are 0.123 and -0.237. The finding in this study indicated that the simulation model needed improvement to be able to estimate the CH4 and N2O emissions from Indonesia’s environmental condition.